Case Report: Endoluminal removal of a conical retrievable superior vena cava filter with a retraction hook attached to the wall - Tian, Xuan; Liu, Jianlong; Li, Jinyong; Liu, Xiao; Zhou, Mi; Tian, Yule (Frontiers in Cardiovascular Medicine, 2024)
We report the case of a 22-year-old male who underwent endoluminal surgery and 21 was implanted an Option Elite filter in the superior vena cava (SVC) while the filter 22 retraction hook was attached to the vessel wall. The patient requested to remove the 23 filter after 155 days. Preoperative ultrasonography and CT examination revealed that 24 the filter retraction hook was very likely to penetrate the SVC wall and its tip was very 25 close to the right pulmonary artery. The SVC was not obstructed, and no thrombus was 26 observed in either upper limb. After the filter retrieval device (ZYLOX, China) failed 27 to capture the filter hook, we introduced a pigtail catheter with its tip partly removed 28 and a loach guidewire, used a modified loop-snare technique to cut the proliferative 29 tissues and free the hook, and finally removed the filter successfully by direct 30 suspension of the guidewire. During this procedure, the patient experienced discomfort, 31 such as chest pain and palpitations, but these symptoms disappeared when procedure 32 completed. Repeated multiangle angiography revealed no contrast medium 33 extravasation, no complications such as pericardial tamponade, pleural effusion, SVC 34 haematoma formation, right pulmonary artery dissecting aneurysm, or intramural 35 haematoma. We initially presented the modified loop-snare technique used to remove a 36 conical superior vena cava filter (SVCF), so this method can be considered a practical 37 and novel auxiliary technique for successful filter retrieval.